A cross-sectional study on the quality of life of women with endometriosis in Trinidad and Tobago - Khan, Raveed; Baksh, Rameez; Wallace, Terika J.; Aimable, Mikael; Bujhawan, Vineeta; Cumberbatch, Justin; Marbella, Enrie Julian; Phagoo, Dana; Ramjattan, Sanathkumar; Shavili, Akshita (Frontiers in Global Women's Health, 2024)
Introduction Endometriosis is a chronic gynecological condition that lacks a definitive cure and adversely impacts the quality of life (QoL) of those affected. This study delves into the experiences of individuals with endometriosis in Trinidad and Tobago, focusing on their quality of life, pain severity, and acceptance of illness. Methods Surveys were distributed among 160 members of the Trinidad and Tobago Endometriosis Association. The survey instrument utilized was the WHOQOL-BREF, which measures QoL, pain severity, and acceptance of illness [the Acceptance of Illness Scale (AIS)]. Results The average age of respondents was 38.65 years. Quality of life scores averaged 3.41, with the “environment” aspect scoring highest (12.84) and “social relationships” scoring lowest (11.88). Cronbach's alpha indicated excellent internal consistency for “environment” (ɑ = 0.909) and the “AIS” (ɑ = 0.882). The independent samples t-test revealed lower mean QoL scores for unemployed participants. Analysis of variance revealed significant differences in mean QoL scores for “health status” and “years since endometriosis diagnosis.” All the QoL domains were positively correlated with each other. There were moderate positive correlations between the physical health and social relationships domains (ρ = 0.558). All other domains were strongly correlated with each other (0.6 < ρ < 0.8). Pain intensity and acceptance of illness had mean scores of 24.15 and 6.57, respectively. Variations in quality of life were observed for health status and duration since diagnosis, impacting mostly on the domain of physical health. Acceptance of illness emerged as a significant influencer of overall quality of life, assisting individuals in navigating the challenges posed by endometriosis. Discussion The findings underscore the importance of understanding determinants, such as pain severity to improve care and support for those with endometriosis. Exploring acceptance of illness is critical in improving the quality of life of these individuals, highlighting the need for tailored interventions that encompass psychological and social support alongside medical treatment. This study demonstrates the pivotal role of acceptance of illness in the overall quality of life of endometriosis patients. Improving the quality of care requires a comprehensive understanding of the factors influencing quality of life, particularly pain severity and the need for a holistic approach to support individuals grappling with endometriosis.